The study of oropharyngeal pack soaked in lignocaine with dexamethasone in patients undergoing nasal surgeries - Agrawal, Mahendra; Gandhi, Pushpal; Agrawal, Bhavika; Behl, Simarn (International Journal of Advances in Medicine, 2020)
Background: The aim of this study determines the efficacy of lignocaine lignocaine with dexamethasone used topically in form of oropharyngeal pack in reducing postoperative sore throat (POST), hoarseness and throat irritation. Methods: This retrospective study total of 70 adult patients included in the lignocaine and dexamethasone (LD) group. LD group patients received combination of 5 ml lignocaine 2% and 2 ml (8 mg) dexamethasone in oropharyngeal packing. Results: There is no significant difference in age, gender, and American society of anesthesiologists (ASA) grade I and II. There was no significant difference the studied group in term of measured hemodynamic indices Systolic blood pressure, diastolic blood pressure, pulse rate, and respiratory rate. Post extubation incidence of mild sore throat was occurred in patients 11 (31.4%) at 30 min, 13 (37.1%) at 2 hours, 6 (17.1%) at 6 hours, and 5 (14.2%) at 5 (14.2%). Moderate sore throat and severe sore throat was not present. Hoarseness of voice was present only 4 (11.4%) at 30 min. There was significant deference in throat irritation. A decrease in incidence of hoarseness was also seen in group LD. Conclusions: In LD group a positive beneﬁt is seen in form of reduction of POST, hoarseness and throat irritation helping in better recovery of patients.